2018
DOI: 10.1097/ijg.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sociodemographic Factors on Disease Characteristics and Vision-related Quality of Life in Primary Open-angle Glaucoma Patients: The Italian Primary Open Angle Glaucoma Study (IPOAGS)

Abstract: Age and sex were significantly associated with almost all indicators of glaucoma severity at baseline. Other variables, such as employment, profession, and marital status were significantly associated with vision-related QoL scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
2
12
0
5
Order By: Relevance
“…Although there are no published studies specifically evaluating how marital status relates to ocular tumor survival, research has suggested that marital status can impact the advancement of ocular disease and visual impairment. [17][18][19] Studies evaluating marital status in the context of non-ocular cancers demonstrate findings similar to ours, with improved outcomes in married individuals compared to non-married individuals. [4][5][6][7] One study of non-small cell lung cancer patients found improved overall and cause-specific survival in married patients compared to non-married patients.…”
Section: Discussionsupporting
confidence: 81%
“…Although there are no published studies specifically evaluating how marital status relates to ocular tumor survival, research has suggested that marital status can impact the advancement of ocular disease and visual impairment. [17][18][19] Studies evaluating marital status in the context of non-ocular cancers demonstrate findings similar to ours, with improved outcomes in married individuals compared to non-married individuals. [4][5][6][7] One study of non-small cell lung cancer patients found improved overall and cause-specific survival in married patients compared to non-married patients.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, we incidentally found a greater number of defective locations within the 10-2 grid compared to the 24-2 in males compared to females across the entire cohort. The role of gender in glaucoma severity in open angle glaucoma remains contentious in the literature, 53,54 and thus this particular result may be another characteristic of the present cohort. Similarly, we had a restricted range of refractive errors in the present study.…”
Section: Limitationsmentioning
confidence: 77%
“…However, when Rasch analysis of the English version was performed in Australian [20] and Indian [21] glaucoma populations, poor psychometric properties were reported. Despite the observed drawbacks, the GSS questionnaire is still being used in recent studies in its original form [2224].…”
Section: Introductionmentioning
confidence: 99%